Molecular mechanism of GylR-mediated regulation of glycerol metabolism in Streptomyces clavuligerus NRRL 3585 - Zhang, Chaobo; Zhao, Youbao; Li, Zilong; Wang, Weishan; Huang, Ying; Pan, Guohui; Fan, Keqiang (Frontiers in Microbiology, 2022)
Glycerol is a readily available and low-cost simple polyol compound, which can be used as a carbon source for microorganisms to produce various value-added products. Understanding the underlying regulatory mechanism in glycerol metabolism is critical for making better use of glycerol for diverse applications. In a few reported Streptomyces strains, the glycerol utilization gene cluster (glp operon) was shown to be regulated by the IclR family transcriptional regulator GylR. However, the molecular regulatory mechanism mediated by GylR has not been fully elucidated. In this study, we first analyzed the available Actinobacteria genomes in the NCBI Genome database, and found that the glp operon-like gene clusters are conserved in Streptomyces and several other genera of Actinobacteria. By taking Streptomyces clavuligerus NRRL 3585 as a model system, we identified that GylR represses the expressions of glp operon and gylR by directly binding to their promoter regions. Both glycerol-3-phosphate and dihydroxyacetone phosphate can induce the dissociation of GylR from its binding sequences. Furthermore, we identified a minimal essential operator site (a palindromic 18-bp sequence) of GylR-like regulators in Streptomyces. Our study for the first time reported the binding sequences and effector molecules of GylR-like proteins in Streptomyces. The molecular regulatory mechanism mediated by GylR presumably exists widely in Streptomyces. Our findings would facilitate the design of glycerol utilization pathways for producing valuable products. Moreover, our study provided new basic elements for the development of glycerol-inducible regulatory tools for synthetic biology research in the future.